Ceramics and Society A Technological Approach to Archaeological Assemblages - Roux, Valentine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Pottery is the most ubiquitous find in most historical archaeological excavations and serves as the basis for much research in the discipline. But it is not only its frequency that makes it a prime dataset for such research, it is also that pottery embeds many dimensions of the human experience, ranging from the purely technical to the eminently symbolic. The aim of this book is to provide a cutting-edge theoretical and methodological framework, as well as a practical guide, for archaeologists, students and researchers to study ceramic assemblages. As opposed to the conventional typological approach, which focuses on vessel shape and assumed function with the main goal of establishing a chronological sequence, the proposed framework is based on the technological approach. Such an approach utilizes the concept of chaîne opératoire, which is geared to an anthropological interpretation of archaeological objects. The author offers a sound theoretical background accompanied by an original research strategy whose presentation is at the heart of this book. This research strategy is presented in successive chapters that are geared to explain not only how to study archaeological assemblages, but also why the proposed methods are essential for achieving ambitious interpretive goals. In the heated debate on the equation stating that "pots equal people", which is a rather fuzzy reference to assumed relationships between (mostly) ethnic groups and pottery, technology enables us to propose with conviction the equation "pots equal potters". In this way, a well-founded history of potters is able to achieve a much better cultural and anthropological understanding of ancient societies.
Introduction to Ceramic Technology -- Description of the Chaînes Opératoires -- Identification of the Chaînes Opératoires -- Classification of Archaeological Assemblages According to the Chaîne Opératoire Concept: Functional and Sociological Characterization -- Technical Skills -- Anthropological Interpretation of Chaînes Opératoires.
Keywords: Archaeology; Archaeology